2019
DOI: 10.1016/j.euroneuro.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in the dorsolateral prefrontal cortex in elderly chronic schizophrenia

Abstract: Cognitive deterioration and symptom progression occur in schizophrenia over the course of the disorder. A dysfunction of the immune system/neuroinflammatory pathways has been linked to schizophrenia (SZ). These altered processes in the dorsolateral prefrontal cortex (DLPFC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 76 publications
3
25
1
Order By: Relevance
“…Thus, our analysis suggested the role of IL-10 as an endogenous regulator of the KP in PFC and CB, although at a different level. Decreased protein and mRNA expression of IL-10 in SZ has been also reported previously at mRNA level in PFC, as well as no differences in IL-1β, as in our experimental conditions [21, 30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, our analysis suggested the role of IL-10 as an endogenous regulator of the KP in PFC and CB, although at a different level. Decreased protein and mRNA expression of IL-10 in SZ has been also reported previously at mRNA level in PFC, as well as no differences in IL-1β, as in our experimental conditions [21, 30].…”
Section: Discussionsupporting
confidence: 89%
“…Differences in the protein expression levels of the downstream member between the group with samples with the highest protein levels and that with the lowest protein levels were evaluated. Significant correlations in this co-expression analysis indicate that the interaction distance between these two proteins is short in this network [30]. The pathway was “coupled” when all the downstream members of the pathway correlate with the upstream member, reflecting the proximity of the members in the pathway.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, area of nucleus of microglial cells was correlated negatively significantly with age in the SPPS subgroup. Neuroinflammation has recently been reported in the PFC in elderly chronic schizophrenia patients (88). Taken together, these data suggest that microglia is involved in a progressive course of schizophrenia.…”
Section: Discussionmentioning
confidence: 54%
“…Previous reviews by Trepanier and Van Kesteren reported evidence for an increased microglial density in SCZ (Trépanier et al, 2016; Van Kesteren et al, 2017). Here, we included 10 additional studies (Brisch et al, 2017; Durrenberger et al, 2015; Fiorentino et al, 2016; López‐González et al, 2019; Nakatani et al, 2006; Petrasch‐Parwez et al, 2020; Schmitt et al, 2011; Schnieder et al, 2014; Seredenina et al, 2017; Sinkus, Adams, Logel, Freedman, & Leonard, 2013) and excluded two studies with overlapping samples (Gos et al, 2014; Steiner et al, 2008), as well as one study that had a strong effect in the previous reviews (ES: 1.79 95% CI 0.76–2.83), but was retracted because of data falsification (Rao, Kim, Harry, Rapoport, & Reese, 2013). In addition, we applied a nesting approach on studies including multiple brain regions.…”
Section: Discussionmentioning
confidence: 99%